Treatment and Imaging Modalities of Giant Coronary Aneurysms Resulting from Kawasaki Disease and Presenting as Acute Inferior Wall Myocardial Infarction - Mahmood Abu Akel; Yaron M. Hellman; Shtiwi Sawaed; Erez Sharoni; Amnon Eitan; Moshe Y. Flugelman (Case Reports in Cardiology)
Giant coronary aneurysms are late sequelae of Kawasaki disease (KD). We describe a 53-year-old patient who presented with acute myocardial infarction and proximal aneurysms of all three coronary arteries. Coronary angiography demonstrated the aneurysms, but CT angiography allowed accurate assessment of the real dimensions of the aneurysms and making the decision on the preferred method of revascularization. The patient underwent coronary bypass surgery and is asymptomatic at follow-up.